(untitled) (Ágora Journal, 2024)
The article analyzes the vision of the Brazilian nation idealized by André Rebouças in two moments: during the years of his involvement in the abolitionist campaign in the 1880s and during the period of his self-exile (1889-1898) after the fall of the monarchy. The first part of the text analyzes the image of the nation constructed by Rebouças as the future result of his social intervention project, aimed at including former slaves and poor immigrants in a Rural Democracy. In his point of view, this imagined community would be more democratic because it would strip away the power of the landowners and guarantee the effective inclusion of marginalized groups in the productive sphere, through access to small land properties. The second part of the text presents the insertion of the figure of D. Pedro II as the hero and protagonist of that model of nation imagined by Rebouças, athwart an idealized vision of the deposed monarchy and its head of state, accompanied by criticism of Republican Brazil.